Tourism Strategies and Local Responses in southern Africa - Hottola, Petri (CABI, 2014)
Development policies appear to be among the most underrated official papers in Southern Africa. When prospecting for authors for this book, I met academics who would not touch the issue of tourism development strategies, even with complete freedom to criticize them. Meanwhile, the Government of Namibia ordered another draft tourism development strategy from a European Union consultant, without any explicit goals for development. According to a common view, governmental and non-governmental organizations create these ‘pamphlets of wishful thinking on a grandiose scale’, print them, make a few speeches and hold press conferences, then bury the strategies deep in the dustbin. As the cynics say, the policy papers are thought to have zero effect on the reality of tourism and the people involved, being mainly published in an attempt to attract development donors. Therefore, one should not waste time on this ‘complete nonsense’, as one of the African academics, a seasoned figure, commented. There is a certain truth in the critical evaluations. At its worst, a tourism development policy may become a strategic way of appearing decisive, while making a firm decision not to make a decision. Moreover, they are frequently riddled with unrealistic expectations. As an example, tourism may be seen as having enormous potential for economic and social development in any location of a nation, however central or peripheral, or whatever the situational context happens to be. Potential there may be, but it is not that easy to harness in a sustainable way. Tourism is not the last-resort magic potion for socioeconomic remedies but a demanding field of economic activity that needs to be addressed in a systematic, professional way. Caution is necessary, too – tourism also has a well-documented ability to bring negative consequences